Derkash's Classification and Vas Visual Analog Scale to Access the Long-Term Outcome of Neurothoracic Outlet Syndrome: A Meta-Analysis and Systematic Review - Lingyun, Wei; Ke, Sha; Jinmin, Zhao; Yu, Qiao; Jun, Qin (Frontiers in Neurology, 2022)
Objective Many publications report outcomes of surgical treatment for neurothoracic outlet syndrome (NTOS); however, high-quality meta-analyses regarding objective evaluation system accessing the long-term outcome of NTOS are lacking. This meta-analysis summarizes and compares the outcomes of Derkosh's classification and vas visual analog scale of the supraclavicular neuroplastic of brachial plexus (SNBP) and trams auxiliary first rib resection (TFRR). Methods The Cochrane Library, PubMed, EMBASE, Allied and Complementary Medicine (AMED) were searched for papers published between January 1980 and February 2021, using the keywords “thoracic outlet syndrome,” “treatment, surgical.” Articles were eligible for inclusion if the following criteria were met studies describing outcomes of surgery for NTOS, published in English, human studies, and available in full text. The exclusion criteria were case reports (n < 10), reviews, abstracts, and studies lacking a control group or without evaluation for two types of surgery. Results We included 10 studies with 1,255 cases, out of which 622 were in the SNBP group; and 633 were in the TFRR group. After surgery (≥12 months), Derkash's classification was improved in 425 cases with SNBP and 364 cases with TFRR. OR = 1.34 (95% CI: 0.94, 1.92), P = 0.03; vas visual analog scale was improved in 282 cases in the SNBP group and 214 cases in the TFRR group. OR = 1.08 (95% CI: 0.63, 1.85), P = 0.78. Conclusion This meta-analysis shows that both SNBP and TFRR are effective for NTOS, but that SNBP is better than TFRR in improving Derkash's classification in the long term. Although patients treated with SNBP are more satisfactory, there is no significant difference in vas visual analog scale from TFRR. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/display_record.asp?ID=CRD42021254203, PROSPERO CRD42021254203.